Pengaruh Model Problem Based Instruction Berbantuan Media Lumio terhadap Kemampuan Pemecahan Masalah Matematis Siswa: Penelitian - Inna Laili Nur Hidayah; Hevy Risqi Maharani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study was to determine the effect of the application of PBI model assisted by Lumio media on mathematical problem solving skills of VII grade students of MTs N 2 semarang. This study used a pre-experiment approach with a One Group Pretest-Posttest design. The results showed a significance value of 0.000 smaller than 0.05, it can be concluded that Ho is rejected. In addition, the average pretest result was 25.08, while the average posttest result increased to 85.40. thus, it can be concluded that the application of PBI model assisted by Lumio media has an effect on students’ mathematical problem solving ability.